Peran Sosial Media sebagai Media Dakwah di Masa Pandemi Virus Corona (Covid-19) di Indonesia - Arman Syah Putra (LP2M UIN Sunan Kalijaga, 2021)
This study discuss the issue of preaching in the midst of corona virus outbreaks or covid-19 on social media. As a impact of the spread of corona virus around the world, many activities outside were restricted to stay at home to break the spread of corona virus and spreading it out to the whole world in general and Indonesia in particular. Almost all aspects of work are prohibited from leaving the house, and only important, broad jobs are still permissible such as doctors and nurses. The method used in this research is to conduct a literature review study in looking at the latest research in the use of social media in conducting da'wah, but this time preaching with social media in the midst of the corona virus outbreak. The writer wants to know whether social media in da'wah can be effective in the midst of a corona virus outbreak that does not yet know when it will end.[Penelitian ini, penulis mengangkat isu dakwah di tengah merebaknya virus corona atau covid-19 di media sosial. Sebagai dampak dari penyebaran virus corona di seluruh dunia, banyak aktivitas di luar yang dibatasi dengan harus berdiam diri di rumah untuk memutus penyebaran virus corona demi menekan menyebarkannya. Hampir semua aspek pekerjaan dilarang keluar rumah, dan hanya yang penting yang diperbolehkan seperti dokter dan perawat. Metode yang digunakan dalam penelitian ini adalah dengan melakukan studi literatur dalam melihat penelitian terbaru mengenai penggunaan media sosial dalam berdakwah di tengah merebaknya virus corona. Penulis ingin mengetahui apakah media sosial dalam berdakwah bisa efektif di tengah wabah virus corona yang belum tahu kapan akan berakhir.]